Evaluation of antirrhinum genotypes for horticultural and phyto-chemical traits - KUMAR, R; Dhiman, M R; Kumar, S; Prakash, C; Kumar, V (Journal of Horticultural Sciences, 2025)
Snapdragon (Antirrhinum majus L.) is a commercially prized specialty cut flower in the international market. Among the inbred lines created, KTANT-2, KTANT-5, KTANT-6, KTANT-8, and KTANT-11 exhibited suitability for different horticultural traits. Total phenolic content in different genotypes ranged from 4.81 to 8.63 gallic acid equivalents (GAE)/100 g dry weight, while, total flavonoid content varied from 56.32 to 164.18 quercetin equivalents (mg/100 g QE). Antioxidant potential was determined through FRAP, DPPH, and MCA analysis. Additionally, FTIR analysis was conducted to identify the presence of various functional groups and compounds.